2018
DOI: 10.1111/sdi.12738
|View full text |Cite
|
Sign up to set email alerts
|

Dialysate potassium concentration: Should mass balance trump electrophysiology?

Abstract: Nephrologists are faced with a difficult dilemma in choosing the ideal dialysis prescription to maintain neutral potassium mass balance. Should potassium mass balance goals prioritize the normalization of serum potassium levels using low potassium dialysate at the expense of provoking intradialytic arrhythmias, or should mass balance goals favor permissive hyperkalemia using higher dialysate potassium to avoid rapid intradialytic fluxes at the risk of more interdialytic arrhythmias? This review examines the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…As expected, we found that dialysis sessions caused a significant decrease of plasma K concentrations. The increase in dialysate K was associated with a lesser decrease in plasma K concentrations [ 12 , 13 , 28 , 30 , 42–46 ], and accordingly with a much lower prevalence of post-dialysis hypokalaemia, including severe hypokalaemia (plasma K <3.0 mEq/L in 6 versus 38% of cases). The higher post-dialysis K concentrations observed with higher dialysate K was accompanied by only a modest and non-significant increase in pre-dialysis plasma K concentrations (and a non-significant higher prevalence of hyperkalaemia).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As expected, we found that dialysis sessions caused a significant decrease of plasma K concentrations. The increase in dialysate K was associated with a lesser decrease in plasma K concentrations [ 12 , 13 , 28 , 30 , 42–46 ], and accordingly with a much lower prevalence of post-dialysis hypokalaemia, including severe hypokalaemia (plasma K <3.0 mEq/L in 6 versus 38% of cases). The higher post-dialysis K concentrations observed with higher dialysate K was accompanied by only a modest and non-significant increase in pre-dialysis plasma K concentrations (and a non-significant higher prevalence of hyperkalaemia).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkalaemia before dialysis session is frequent, dangerous and increases morbidity and mortality [ 7 , 17 , 18 , 22–30 ]. Additional data also suggest that pre-dialysis hypokalaemia, although less frequent, could be associated with higher mortality [ 11 , 13 , 22 , 25 , 27 , 30–32 ]. The risk of post-dialysis hypokalaemia is much less well studied and thus its prevalence is not precisely known [ 11 , 31 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As new technologies allow greater opportunities to alter dialysate constituents, dialysate prescription has also been evolving. On the topic of dialysate potassium concentration, Pun reviews the currently available approaches for managing potassium mass balance while reducing risk of arrhythmias by examining the factors that determine potassium mass balance and assessing the relationship between serum and dialysate potassium levels and outcomes …”
mentioning
confidence: 99%